2020
DOI: 10.1371/journal.pone.0230924
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endophytic bacterial diversity in rose by high-throughput sequencing analysis

Abstract: The endophytic bacterial diversity of rose was analyzed by high-throughput sequencing of 16S rDNA and functional prediction of the bacterial community. The number of bacterial sequence reads obtained from 18 rose samples ranged from 63,951 to 114,833, and reads were allocated to 1982 OTUs based on sequences of the V3-V4 region. The highest Shannon Index was found in Luogang rose (1.93), while the lowest was found in Grasse rose (0.35). The bacterial sequence reads were grouped into three different phyla: Firmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…These discrepancies may be attributed to variances in production techniques, fermentation conditions, and microbes present in rose. Xia et al (2020) employed throughput sequencing of 16S rDNA to reveal substantial differences in bacterial diversity across various regions where roses were grown. In a study conducted by Ramos et al (2020), next‐generation sequencing was utilized to analyze the impact of three different concentrations of cupuassu pulp fermentation (0%, 7.5%, and 15%) on microbial diversity (Ramos et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These discrepancies may be attributed to variances in production techniques, fermentation conditions, and microbes present in rose. Xia et al (2020) employed throughput sequencing of 16S rDNA to reveal substantial differences in bacterial diversity across various regions where roses were grown. In a study conducted by Ramos et al (2020), next‐generation sequencing was utilized to analyze the impact of three different concentrations of cupuassu pulp fermentation (0%, 7.5%, and 15%) on microbial diversity (Ramos et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the microbiome of Rosa spp. consists of bacteria, such as Bacillus and Staphylococcus (Xia et al, 2020), as well as fungi (Zhao et al, 2018). Furthermore, hyperproduction of peroxidase in the young D. rosae larvae may be regarded as a response to the defensive mechanisms of the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…PICRUSt function prediction found that carbohydrate metabolism and energy metabolism functional genes were abundant in endophytic fungi in ordinary A. sinensis and Qi-Nan. Genes relevant to metabolism can influence plant growth, and beneficial microbes can synthesize and secrete secondary bioactive metabolites that maintain host plant health [70]; the endophytic fungi of Qi-Nan and ordinary A. sinensis perform such functions. In addition, studies have demonstrated that the process of agarwood formation involves carbohydrate metabolism in order to produce secondary metabolites.…”
Section: Endophytic Fungi Of Grafting Seedlingsmentioning
confidence: 99%